Out-of-pocket costs and adherence to antihypertensive agents among older adults covered by the public drug insurance plan in Quebec - Milan, Raymond (Patient Prefer Adherence, 2017)
OBJECTIVE: To evaluate the effect of patient out-of-pocket costs on adherence to antihypertensive agents (AHA) in community-dwelling older adults covered by the public drug insurance plan in Quebec. METHODS: This is a secondary analysis of data from the “Étude sur la santé des aînés” study (2005–2008) on community-dwelling older adults in Quebec aged 65 years and older (N=2,811). The final sample included 881 participants diagnosed with arterial hypertension and treated with AHA. Medication adherence was measured with the proportion of days covered over a 2-year follow-up period (<80% and ≥80%). Out-of-pocket costs for AHA, in Canadian dollars (CAD), at cohort entry were categorized as follows: $0, $0.01–$5.00, $5.01–$10.00, $10.01–$15.00 and $15.01–$36.00. Multivariable logistic regression models were constructed to study adherence to AHA as a function of out-of-pocket costs while controlling for several confounders. Models were also stratified by annual household income (<$15,000 CAD and ≥$15,000 CAD). RESULTS: In this study, 80.8% of participants were adherent to their AHA. Among participants reporting an annual household income <$15,000 CAD, those with an out-of-pocket cost of $10.01–$15.00 CAD were significantly less adherent to their AHA than those with no contribution (OR =0.175, 95% CI: 0.042–0.740). Among participants reporting an income of ≥$15,000 CAD, those with out-of-pocket costs of $0.01–$5.00 CAD (OR =0.194; 95% CI: 0.048–0.787), $5.01–$10.00 CAD (OR =0.146; 95% CI: 0.036–0.589), $10.01–$15.00 CAD (OR =0.192; 95% CI: 0.047–0.777) and $15.01–$36.00 CAD (OR =0.160, 95% CI: 0.039–0.655) were significantly less adherent to their AHA than participants with no contribution. CONCLUSION: Increased out-of-pocket costs are associated with non-adherence to AHA in older adults covered by a public drug insurance plan, more importantly in those reporting an annual household income ≥$15,000 CAD. A reduction in the amount of out-of-pocket costs and yearly maximum contribution for drugs may improve adherence to treatment.